Сomparison of GEANT4 with EGSnrc for simulation of gamma-radiation detectors based on semi-insulating materials - Skrypnyk, A.I.; Zakharchenko, A.A.; Khazhmuradov, M.A. (Вопросы атомной науки и техники, 2011)
We considered GEANT4 version 4.9.4 with different Electromagnetic Physics Package for calculation of response functions of detectors based on semi-insulating materials. Computer simulations with GEANT4 packages were run in order to determine the energy deposition of gamma-quanta in detectors of specified composition (HgI2 and TlBr) at various energies from 0.026 to 3 MeV. The uncertainty in these predictions is estimated by comparison of their results with EGSnrc simulations. A general good agreement is found for EGSnrc and GEANT4 with Penelope 2008 model of LowEnergy Electromagnetic package. Досліджено можливості різних моделей електромагнітної взаємодії гамма-квантів у GEANT4 v.4.9.4 для розрахунку функцій відгуку детекторів на основі напівізолюючих матеріалів. GEANT4 використано для визначення втрат енергії гамма-квантами в детекторах з HgI2 і TlBr в діапазоні енергій від 0,026 до 3 МеВ. Похибки розрахунків GEANT4 було оцінено шляхом порівняння з даними моделювання EGSnrc. Виявлено добру відповідність між розрахунками EGSnrc та GEANT4 при використанні моделі електромагнітної взаємодії Penelope 2008. Исследованы особенности различных моделей электромагнитных взаимодействий гамма-квантов в GEANT4 v.4.9.4 для расчета функций отклика детекторов на основе полуизолирующих материалов. GEANT4 использован для определения потерь энергии гамма-квантов в детекторах из HgI2 и TlBr в диапазоне энергий от 0,026 до 3 МэВ. Погрешности расчетов GEANT4 оценивались при сравнении с данными моделирования EGSnrc. Хорошее согласие обнаружено между расчетами EGSnrc и GEANT4 при использовании модели электромагнитных взаимодействий Penelope 2008.